Energy, nutrient and overall healthiness of processed packaged foods in Fiji, a comparison between 2018 and 2020 - Aliyah Palu; Joseph Alvin Santos; Ana Moala Silatolu; Alvina Deo; Colin Bell; Gade Waqa; Jacqui Webster; Briar L. McKenzie (BMC, 2024)
Abstract In Fiji, packaged foods are becoming increasingly available. However, it is unknown if nutrition composition of these foods has changed. This study aims to assess changes in energy, nutrient content and healthiness of packaged foods by comparing data from five major supermarkets in Fiji in 2018 and 2020. Foods were categorised into 14 groups; nutrient composition information was extracted and healthiness assessed using Health Star Rating (HSR). Descriptive statistics and a separate matched products analysis was conducted summarising differences in nutrient content and HSR. There was limited evidence of change in the nutrient content of included products however, there was a small reduction in mean saturated fat in the snack food category (-1.0 g/100 g, 95% CI -1.6 to -0.4 g/100 g). The proportion of products considered healthy based on HSR, increased in the convenience foods category (28.4%, 95% CI 8.3 to 48.5) and decreased in non-alcoholic beverages (-35.2%, 95% CI -43.6 to -26.9). The mean HSR score increased in the fruit and vegetables category (0.1 (95% CI 0.1, 0.2)) and decreased for non-alcoholic beverages (-1.1 (-1.3, -0.9)) and the sauces, dressings, spreads, and dips category (-0.3 (-0.3, -0.2)). Strengthened monitoring of the food supply is needed to improve the healthiness of foods available.